Evaluasi Penerapan Sistem Informasi Manajemen Puskesmas (SIMPUS) - Ahmad Hikmi Aldio; Deasy Rosmala Dewi; Noor Yulia; Wiwik Viatiningsih (Cerdika: Jurnal Ilmiah Indonesia, 2022)
In evaluating the implementation of the Puskesmas Management Information System (SIMPUS) at the puskesmas, it is expected to be able to minimize the accumulation of patients the health service procedures at the puskesmas and also to foster more enthusiasm for the officers at the puskesmas so that services become more effective. So it is necessary to evaluate the implementation of the health center management information system (SIMPUS). Objective: evaluate the implementation of the puskesmas management information system (SIMPUS) to find out what methods are used in evaluating the implementation of the puskesmas management information system (SIMPUS). This study uses the google scholar database in computing a literature review search by using the keyword search for this research journal, namely ” Evaluation of applications (SIMPUS) at the puskesmas. Research results in it can be seen that the most dominant SIMPUS evaluation used is Hot-fit while the least is the cloud-based methods in evaluating the implementation of the puskesmas management information system (SIMPUS). The puskesmas management evaluation information system (SIMPUS) has several methods in implementing the SIMPUS evaluation, namely, web-based, hot-fit, and cloud-based.